A remark on the Gersten complex for Milnor K -theory - Pawar, Rakesh (Mathematical Sciences Publishers, 2022)
We consider the Gersten complex for Milnor K-theory over a regular local Henselian domain S and prove that in degrees ≥ dim S ≥ 1 , the Gersten complex of an essentially smooth Henselian local S-scheme is exact.
Only IISER Mohali authors are available in the record.
Keywords: Gersten complex; Milnor K -theory